Microfinancing and Poverty Alleviation: A Case of Advans Savings and Loans Limited in Sunyani - Mahi Bawa; Oscar Agyemang Opoku (Garuda Prestasi Nusantara Consulting, 2023)
The study examined the effect of microfinance on poverty alleviation in Sunyani Municipal using Advans Savings and Loans Limited. The study employed descriptive survey of the quantitative approach. Convenience sampling was used to select 243 respondents to form part of the study. Questionnaire was used as a data collection instrument to solicit for data from the market operators. The data gathered from the respondents were analyzed descriptively using frequencies, percentages and means as well as paired sample t-test with the aid of Statistical Package for Service Solution software version 21.0. The study found that household’s income, agribusiness, productivity and paying of utility bills have been improved after the introduction of microfinance service. Households’ daily savings, frequent of savings, and amount of savings have been improved subsequently after accessing microfinance products. There has been an improvement in the acquisition of assets after households started to patronize microfinance services. Respondents’ livelihoods have been influenced positively. There has been an appreciable improvement in financial, human and physical assets but little influence on natural and social assets. Therefore, the study recommended that microfinance should develop and improve upon packages and products for households in order to improve upon their income levels as well as acquisition of basic household assets. Moreover, households should be sensitized and educated on the essence of investing in social assets as well as social assets in the society.